Estudio de factibilidad, para la creación de una empresa de servicios en capacitación y orientación empresarial para las pequeñas empresas de la ciudad de Armenia (2015)
Because of the development of the city, the required studies were made in order to determine the feasibility of creating the company of EXITO EMPRESARIAL SAS, which is dedicated in rendering services such as training and business counseling for small businesses in the city of Armenia. This project is specifically designed for small businesses in the city of Armenia that require such services. According to the delimitation made, it was established that there are 728 small businesses that are reachable for the training and counseling services, where a survey was made just to try to identify and determine the trends, meaning that in this group of businesses the fieldwork was done. After conducting the market research, other steps were taken making all together a feasibility study, meaning the technical study which covers size, location and engineering, which is needed in order to operate in the administrative, legal and environmental studies which develops the main elements that give the beginnings of the company formally, and it ends the project with the financial feasibility of it using indicators such as VPN, TIR and the relation between benefit and cost.